Peran PIK-R Sebagai Wadah Konseling: Implementasi Kegiatan Sosialisasi: Sehat Jiwa Dimulai Dari Lingkungan Sekolah - Ria Yuni Lestari; Huldah Nilan Setianingrum; Nur Farida; Nizar Ali Isnaini; Tati Rohmayanti (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
Social media plays an active role in providing positive and negative impacts on young people. According to Jannah (2020), as many as 48% or 130 million of the human population on earth use social media. Young people use social media to communicate and exchange information. By using qualitative research methods, it is hoped that the goals of students know that PIK-R exists as a forum for counseling. Salmiati, Hasbahudin in 2018 said that mentoring and counseling are strategies for solving student problems at school. Coupled with peer counselors who can help optimize counselor performance. However, in this study, the researchers found that there were students who did not know the role, function, or even extracurricular activities of PIK-R.